2015
DOI: 10.1109/tec.2015.2441040
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Equivalent Circuit Modeling of the AC Homopolar Machine for Flywheel Energy Storage

Abstract: This paper develops a magnetic equivalent circuit model suitable to the design and optimization of the synchronous ac homopolar machine. The ac homopolar machine is of particular interest in the application of grid-based flywheel energy storage, where it has the potential to significantly reduce self-discharge associated with magnetic losses. The ac homopolar machine features both axial and radial magnetizing flux paths, which requires finite element analysis to be conducted in 3-D. The computation time associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 37 publications
0
29
0
2
Order By: Relevance
“…A lo largo del siglo XX su uso se limitó a aplicaciones tales como la fusión eléctrica, soldadura eléctrica y tratamientos térmicos que requerían fuentes de alimentación con frecuencias comprendidas entre 1.000 y 10.000 Hz (Walker, 1946). Actualmente hay un renovado interés por los AI, que se están utilizando en los sistemas de iluminación y aire acondicionado de los ferrocarriles (Pillai et al, 2008), en grandes vehículos especiales para minería y obra civil (Milspec Manufacturing) y, especialmente, en aplicaciones a altas velocidades de rotación, acoplados a un volante de inercia (Severson et al, 2015) o al eje de una turbina de gas, en generadores superconductores (Sivasubramaniam et al, 2009). …”
Section: El Alternador Inductorunclassified
“…A lo largo del siglo XX su uso se limitó a aplicaciones tales como la fusión eléctrica, soldadura eléctrica y tratamientos térmicos que requerían fuentes de alimentación con frecuencias comprendidas entre 1.000 y 10.000 Hz (Walker, 1946). Actualmente hay un renovado interés por los AI, que se están utilizando en los sistemas de iluminación y aire acondicionado de los ferrocarriles (Pillai et al, 2008), en grandes vehículos especiales para minería y obra civil (Milspec Manufacturing) y, especialmente, en aplicaciones a altas velocidades de rotación, acoplados a un volante de inercia (Severson et al, 2015) o al eje de una turbina de gas, en generadores superconductores (Sivasubramaniam et al, 2009). …”
Section: El Alternador Inductorunclassified
“…HSM have robust rotor design and due to their lower standby losses compared to PMSM, they can be used an alternative to PMSM in high-speed applications [25,30]. However, the main disadvantage is the difficult design of HSM due to its complex magnetic flux paths and geometry [31].…”
Section: Introductionmentioning
confidence: 99%
“…In 1 study, the modified WFT has been proposed for machines with the asymmetrical air gap by Faiz et al but saturation effect has been neglected. Recently, there have been some new investigations on MEC modeling besides WFT and FEM . In these researches conducted in MEC modeling area, the magnetic and electric equations have been considered separately and some technical approaches have been used for their coupling.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the performance of the mesh‐based model is more effective than of the nodal‐based model under nonlinear operation. Magnetic equivalent circuit modeling of the healthy AC homo‐polar machine considering saturation effect has been presented in 1 study, but the faulty machine has been not studied. In 1 study, a hybrid model has been addressed on the basis of Fourier modeling combination method with mesh‐based MEC method but linear core characteristics have been used; therefore, saturation effect has been not considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation